Sustainable transitions in food systems: a case study of an urban agriculture farming training program in Washington, United States - Keefe, Soumya; Lee, Jean (Frontiers in Sustainable Food Systems, 2025)
A transition toward more sustainable and just food system is necessary to address global greenhouse gas emissions and inequitable food access. Alternative food networks have emerged as a solution to counteract the adverse impacts of conventional food systems. Urban agriculture is a type of alternative food network that strives to provide local access to food through the development of community gardens or community-supported agriculture. Farmer training programs are uniquely positioned to build the capacity of those who are interested in engaging in urban agriculture, yet little is known about whether these programs—and their graduates—contribute to sustainability transitions within the food system. We build on previous scholarship that establishes the importance of farmer training programs and use a training program in Washington, United States to understand how these programs support and encourage sustainability transitions. The multi-level perspective breaks down systems into landscape, regime, and niche levels. It provides a framework for understanding the system under which urban agriculture operates and the different actors and institutions that stabilize the existing food regime. Social practice theory emphasizes the importance of focusing on how change occurs at the local level. We use a combination of the multi-level perspective framework and social practice theory to explicate how multi-scalar dynamics of food systems pose barriers and allows for opportunities for actors at a local level to exert change on the larger system. Our results show that training programs allow a space for social learning and changes the collective practices and narratives among its graduates. We also find that the potential for graduates to exert larger change on the regime is curtailed due to the training program’s limited capacity to exert vertical pressure on the systems. For regime change to occur, state and local government need to intentionally support policies that recognize the importance of urban agriculture in their sustainability agendas.